2016
DOI: 10.1021/acs.inorgchem.5b02594
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Bronze Barium Neodymium Titanate (Ba6–3nNd8+2nTi18O54): An Intrinsic Nanostructured Material and Its Defect Distribution

Abstract: We investigated the structure of the tungsten bronze barium neodymium titanates, Ba 6-3n Nd 8+2n Ti 18 O 54 , which are exploited as microwave dielectric ceramics. They form a complex nanostructure, which resembles a nanofilm with stacking layers of approximately 12Å thickness. where the nanostructure and the distribution of the dopants will reduce the thermal conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
(151 reference statements)
1
13
0
Order By: Relevance
“…In figure 1a the most obvious of these is the elongation of the La columns in the LFO layer. This suggests a "zig-zagging" of the La atoms along the beam direction, resulting in "elliptical" atomic columns as seen previously by Azough et al [21]. Fitting 2D Gaussians to every A-site atomic column using the Atomap software [18] yields a map of the ellipticity of the A-cations (La and Sr columns) as shown in Figure 1b, revealing a distinct ellipticity in the LFO, not observed in the STO or the LSMO.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…In figure 1a the most obvious of these is the elongation of the La columns in the LFO layer. This suggests a "zig-zagging" of the La atoms along the beam direction, resulting in "elliptical" atomic columns as seen previously by Azough et al [21]. Fitting 2D Gaussians to every A-site atomic column using the Atomap software [18] yields a map of the ellipticity of the A-cations (La and Sr columns) as shown in Figure 1b, revealing a distinct ellipticity in the LFO, not observed in the STO or the LSMO.…”
Section: Resultssupporting
confidence: 62%
“…Large electron doses can often alter the oxide, and recent work has shown that beam damage to perovskites happens well before it is obvious in high-resolution images [20]. In some cases, 3D information can also be inferred from the shape of the columns in 2 dimensions [10,18,21]. An important drawback for this strategy is that the method requires both very high quality TEM-samples, an optimized aberration corrected STEM and a high degree of post processing to reduce the effects of scanning distortions [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This type of analysis is best suited for monocrystalline materials, especially epitaxial thin films and heterostructures, or polycrystalline materials with large grains (e.g., domain-structured functional oxides with different orientations of the principal axes of the cell), as the technique requires the crystal to be imaged along a zone axis. While it may be performed at atomic resolution, this is not necessary, and this technique has the advantage that it yields information about the modulation of atomic positions along a column without requiring atomic resolution, as demonstrated in previous analyses of this effect (Borisevich et al, 2010; Azough et al, 2016).…”
Section: Higher-order Laue Zone Analysismentioning
confidence: 99%
“…domain-structured functional oxides with different orientations of the principal axes of the cell), as the technique requires the crystal to be imaged along a zone axis. Whilst it may be performed at atomic resolution, this is not necessary, and this technique has the advantage that it yields information about the modulation of atomic positions along a column without requiring atomic resolution, as demonstrated in previous analyses of this effect (Azough et al, 2016;Borisevich et al, 2010).…”
Section: Higher Order Laue Zone Analysismentioning
confidence: 99%